New aspects of nutritional status : 30th symposium of the European Academy of Nutritional Sciences, (formerly GEN), Vienna, July 7-9, 1993 - Somogyi, Johann C; Elmadfa, I; Walter, Paul (Karger, 1994)
The assessment of nutritional status is aimed at detecting the prevalence and/or incidence of malnutrition in the sense of both under-or overnourishment. Data on the nature and extent of prevailing nutritional problems are essential for the formation of nutrition policy and the development of educational programs. This volume, based on the EANS meeting (formerly GEN) held in Vienna, offers the reader broad yet thorough coverage of recent advances in the study of nutritional status. The sections of the book deal with food intake, epidemiology and the assessment of nutritional status. The book concludes with the recommendations of a round table discussion on nutrient and energy intake. Presenting the latest research findings and the opinions of leading nutrition experts, this volume is a valuable resource for nutritionists, clinicians, epidemiologists, dietitians, food chemists and all those interested in this important topic.
Bibliotheca nutritio et dieta ; Vol. 51
Keywords: nutriční terapie, dietoterapie a výživa